Improving Knowledge of Chicken Nugget Processing Using Animated Videos for Junior High School Students - Febriani Anggita Dewi; M Muktiarni; Jonah Mupita (ASEAN Journal of Science and Engineering Education, 2021)
The purpose of this study was to increase the knowledge of junior high school students regarding the processing of chicken nuggets in terms of knowledge of materials, equipment and stages of manufacture. The method used in this research is video animation. This method uses audio-visual so that it can increase students' interest in learning the processing of chicken nuggets. The approach used in this research is quantitative. The results showed that the students' knowledge about processing chicken nuggets increased. This can be seen from the students' post-test results increased by 31.25%. The animated video method given to students provides an explanation of the pictures of tools and materials as well as an explanation of the manufacturing process optimally. Therefore, students can understand the material well.